(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background : Premature Rupture of Membrane (PROM) is one of the most common complication of pregnancy. A woman with premature rupture of membrane is at risk of perinatal morbidity and mortality and also associated with maternal morbidity and psychological stress. Objective of this study was to determine incidence and risk factors of pregnant woman with PROM admitted in a tertiary hospital at Chattogram, Bangladesh. Materials and methods : This prospective observational study conducted in the Department of Obstetrics and Gynaecology at Chattogram Maa-O-Shishu Hospital Medical College (CMOSHMC) Chattogram from 1stJanuary 2018 to 31st December 2018. In this period total admitted antenatal patients were 8117. Among the pregnant patients with PROM were 665 and their weeks of gestation were > 28 weeks. Data was collected by interviewer with semi structured questionnaire & check list. Results : Incidence of PROM was 8.2%. PROM was found to be frequent (53%) in younger age group between 20-24 years. It was also commonly in primigravida (61.8%). Term PROM was higher (69.2%) than pre-term PROM (30.8%). 93.3% were singleton pregnancies, 6.4% were twins and .3% were triplets. Analysis of risk factors revealed ectiology was unknown in 46 (6.8%) low socioeconomic condition (60.6%), anaemia (45 %), lower genital tract infection (35.6%) UTI (31%) previous history of PROM (27.9%) malpresentation (15%) multiple pregnancy (6.7%) polyhydramnios (6%) history of recent coitus (12%) DM and GDM (10.5%) were commonly associated with PROM. Conclusions : Early identification of various risk factors causing PROM and their management can prevent premature deliveries and its complications to some extent as well as serious maternal complication like Chorioamnionitis. Chatt Maa Shi Hosp Med Coll J; Vol.19 (2); July 2020; Page 5-8